2020
DOI: 10.2147/ott.s217452
|View full text |Cite
|
Sign up to set email alerts
|

<p>Down-regulation of lncRNA LINC00152 Suppresses Gastric Cancer Cell Migration and Invasion Through Inhibition of the ERK/MAPK Signaling Pathway</p>

Abstract: The aim of this study was to explore the regulatory role and mechanism of long noncoding RNA LINC00152 in gastric cancer (GC) cells. Methods: LINC00152 expression in GC tissues and cells was detected by reverse transcription-polymerase chain reaction (qRT-PCR). MKN45 and MGC-803 cells were selected and assigned into different groups after transfection with si-LINC00152, activated ERK/MAPK signaling pathway (SA), or negative control. Cell proliferation, apoptosis, cycle, migration and invasion were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Unfortunately, in the early stage of gastric cancer, the rate of lymph node metastasis may exceed 20%. 14 We found that MCU expression was significantly correlated with depth of invasion, lymph metastasis, TNM stage and distant metastasis, indicating that MCU expression could be associated with prognosis of gastric cancer. Intriguingly, our results indicated that MCU expression was significantly higher in omental metastasis than gastric cancer tissues, indicating that MCU expression might contribute to gastric cancer metastasis.…”
Section: Discussionmentioning
confidence: 67%
“…Unfortunately, in the early stage of gastric cancer, the rate of lymph node metastasis may exceed 20%. 14 We found that MCU expression was significantly correlated with depth of invasion, lymph metastasis, TNM stage and distant metastasis, indicating that MCU expression could be associated with prognosis of gastric cancer. Intriguingly, our results indicated that MCU expression was significantly higher in omental metastasis than gastric cancer tissues, indicating that MCU expression might contribute to gastric cancer metastasis.…”
Section: Discussionmentioning
confidence: 67%
“…6,7 For example, lncRNA LINC00152 upregulation promotes gastric cancer growth and metastasis. 8 LncRNA SNHG6 overexpression facilitates lung cancer cell proliferation and metastasis. 9 MiR-340-5p dysregulation promotes tumorigenesis of esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…LINC00152 (long intergenic noncoding RNA 152), transcribed from the region between protein-coding genes PLGLB2 (plasminogen like B2) and PLGLB1 (plasminogen like B1), is also known as CYTOR (cytoskeleton regulator RNA). Through interfering with cell signaling pathways such as PI3K/AKT ( 105 ), FSCN1 (fascin actin-bundling protein 1) ( 106 ), and Wnt/β-catenin ( 107 , 108 ), LINC00152 was demonstrated to promote the invasion and metastasis of diverse tumors. At present, research on the function of LINC00152 in OSCC metastasis is also mainly focused on its role of ceRNAs.…”
Section: Overview Of Lncrnas Involved In Oscc Metastasismentioning
confidence: 99%